PENGARUH KONSENTRASI GULA DAN STARTER TERHADAP PENERIMAAN PANELIS PADA ANGGUR BUAH SEMU JAMBU METE - Puspawati, Ni Nyoman; Sudjatha, Wayan; Timur Ina, Putu (Agrotekno, 2012)
The objectives of this research are: (i) to know the influence of concentration of sugar and starter to heavy metal content; (ii) the level of acceptance by panelists on wine produced from jambu mete; (iii) to know how much sugar and starter should be added in producing wine of jambu mete in order to obtain the most accepted to by panelists. This research was undertaken by using a Complete Random Design with two treatments, namely: sugar concentration (in 3 levels: 15, 20 and 25 %), and starter concentration (in 5 levels: 3, 6, 9, 12 and 15 %). Research results showed that the metal contents of jambu mete juice are as
Keywords: Buah semu jambu mete, cemaran dan karakteristik subyektif